Balancing Economic Growth and Environmental Conservation: Assessing Supportive Policies in Resources-Based Cities in China - Hewang Liu; Xiuyu Li; Shilin Zheng (Systems)
This study investigates the impact of comprehensive reforms on the economic development and environmental protection of resource-based cities in China within the context of the ‘National Sustainable Development Plan for Resource-based Cities (2013–2020)’. Employing a difference-in-differences methodology, we find that these reforms not only bolster economic stability but also significantly enhance urban ecological environment, resulting in a win–win outcome for economic prosperity and environmental preservation. Our analysis reveals that the reforms drive sustained economic growth and ecological enhancement by downsizing industries, adopting green technologies, and optimizing industrial composition. Moreover, we identify that these impacts are more pronounced in mature and declining cities and in regions with robust official promotion strategies and stringent environmental regulations. These findings provide valuable insights for addressing the “resource curse” within social systems and for formulating policies that balance stable economic growth and environmental protection in resource-based cities.